Encyclopedia of distance learning - Howard, Caroline (Idea Group Reference, 2005)
"This encyclopedia offers the most comprehensive coverage of the issues, concepts, trends, and technologies of distance learning. More than 450 international contributors from over 50 countries"--Provided by publisher.